Pengaruh Kredit Modal Kerja Dan Kredit Investasi Terhadap PDRB Sektor Industri Pengolahan Di Kalimantan Barat - B01110048, MUHAMMAD RAZALI (Jurnal Pembangunan dan Pemerataan, 2016)
This study , entitled " Effect of working capital credit and investment credit against GDPManufacturing in West Kalimantan " . This study aims to determine the effect of working capitalcredit and investment credit Against Manufacturing Sector GDP in the period from 1983 to 2012 inWest Kalimantan .This research uses descriptive quantitative method by using secondary data, time series data ,obtained from the office of the Central Statistics Agency of West Kalimantan . The analytical toolused to process the data that is used Eviews 6. Observation of the data as much as 14 districts / citiesin West Kalimantan Province during the period 1983 to 2012 .Multiple regression results of this study indicate that the variable working capital creditpositive and significant impact and variable investment credit positive and significant impact on thesector GDP Processing IndustryKeywords : Working Capital Loan , Investment Loan , GDP and Processing Industry